How social media marketing impact the apartment purchase intention of Generation Z in Ho Chi Minh City - Hoang, Cuu Long; Nguyen, Hong To Nguyen (Journal of Finance - Marketing Research, 2024)
This study has been designed to determine the impact of social media marketing on Gen Z's apartment purchasing intention. The huge proportion of Gen Z who are going to join the workforce shows that they have a significant contribution to the housing demand in Vietnam, especially in Ho Chi Minh City. A sample of 157 people who were born between the year 1996 to 2012 with an average monthly income of 20 million VND, living in Ho Chi Minh City has been drawn randomly. The personal information of the participants is collected through a demographic information sheet. A questionnaire is used to identify which social media marketing attributes affect the behavior toward apartment purchasing, therefore measuring how social media channels influence Gen Z's apartment purchase decision in Ho Chi Minh City. Research results show that the impact of E-Word-of-Mouth, Online advertisement, and Online community on the apartment purchase intent of Gen Z’s customers.